THE EXPERIENCE OF PREGNANCY IN ADOLESCENCE ON FAMILY AND SOCIAL SCOPE - Carolina Carbonell dos Santos; Laís Antunes Wilhelm; Camila Neumaier Alves; Luiza Cremonese; Crislen Malavolta Castiglioni; Larissa Venturini; Carolina Frescura Junges; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2014)
http://dx.doi.org/10.5902/217976929860 Aim: to analyze the experience of teenage pregnancy in the context of a family and social. Method: a descriptive study, developed o a primary care health unity. Criteria inclusion were pregnant adolescents between 10 and 19 years. Eight pregnant women participated. Research project was approved by the Committee of Ethics in Research under the number 00554512.0.0000.5346. Data collection will be performed through a narrative interview, between March and June 2012, and analyzed by using the content analysis technique with thematic. Results: both families and partners of the teenagers, are supporters of the pregnancy, even though, the first pregnancy discover caused doubt and anxiety to teenagers. Final Considerations: the study provides a contribution to the knowledge on teenage pregnancy, family participation and its importance in this phenomenon for source of support.